Significant efficacy of tofacitinib from China in the treatment of alopecia areata: a case report - He, Yijia; Qi, Jinxu; Wu, Zhuochen; Zhang, Jinfang; Zhang, Guoqiang (Frontiers in Immunology, 2025)
Alopecia Areata (AA) is a common form of scarless alopecia. Its pathogenesis may be related to T cell-mediated autoimmune attack on hair follicles. Its clinical manifestations are mostly round or oval patches of AA, which can progress to Alopecia Totalis (AT) and Alopecia Universalis (AU). In severe cases, it affects the psychological health and quality of life of patients. In the past, the treatment of AA mainly relied on intra-lesional or systemic application of glucocorticoids, minoxidil or immunomodulators, which had problems such as limited efficacy and high recurrence rate. Some studies have also found that JAK inhibitors have improved effects on many autoimmune diseases, including AA. This case report presents a patient with AA who achieved significant therapeutic effects from treatment with Tofacitinib Citrate Sustained-Release Tablets, manufactured by Qilu Pharmaceutical Company in China. Due to the recurrence rate of AA, patients are likely to need long-term medication. The resulting economic burden cannot be ignored. We therefore investigated the mechanisms and economic benefits of various JAK inhibitors in the treatment of AA, in order to provide better guidance to patients with recurring disease who need long-term medication, and to their doctors in choosing a more rational therapeutic agent according to the patient’s condition and economic status.